Nasopharyngeal SARS-CoV-2 viral load kinetics using digital PCR - Elizabeth Hastie; Harold Amogan; David Looney; Sanjay R. Mehta (Heliyon, 2023)
Background: The relationship between the viral kinetics of SARS-CoV-2 and clinical outcomes remains unclear. Methods: A convenience sample of 955 remnant nasopharyngeal swabs collected during routine care between 11/18/20 and 9/26/21 were analyzed using digital PCR and associated clinical data extracted from the medical record. 18 individuals had >1 sample within 30 days of onset of symptoms. Results: Paired samples were an average of 6 [range: 0–13] days apart. Four individuals sampled twice on the same day had a median 0.52 log10 viral load difference between samples. Of the remaining, 12 individuals had a decrease in viral load over time, with an average decay of −0.23 log10/day. Conclusions: Our study found a similar rate of viral decay to others, but did not find associations between viral kinetics and clinical outcomes. Larger studies would be useful to support the use of this measurement as a surrogate endpoint for therapeutic studies.